Zirconium oxide powder with uniform particle size distribution and preparation method thereof
By adding urea or ammonium bicarbonate to the hydrolysis reaction of zirconia powder, controlling the pH environment, combining spray drying and sand grinding processes, the problem of uneven particle size distribution of zirconia powder is solved, and a significant improvement in particle size uniformity and agglomeration properties are achieved, meeting the quality requirements of high-end products.
Patent Information
- Application Number
- CN202411773298.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-07
AI Technical Summary
The particle size distribution of existing zirconia powders is uneven, making it difficult to meet the needs of high-end products such as circuit capacitance materials.
By adding urea or ammonium bicarbonate to the hydrolysis reaction, the pH of the system is 7-9, and the slow precipitation and uniform dispersion of zirconium ions are achieved. Combined with spray drying and sand grinding, a zirconium oxide powder with uniform particle size distribution is obtained.
It significantly improves the uniformity of particle size distribution of zirconia powder, reduces particle agglomeration, and meets the quality requirements of high-end products.
Smart Images

Figure CN119569112A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of zirconium oxide preparation, and in particular to zirconium oxide powder with uniform particle size distribution and a preparation method thereof. Background Art
[0002] Zirconium oxide (ZrO2), as a material with high melting point, high boiling point, high density, stable high-temperature chemical properties, corrosion resistance, oxidation resistance, thermal shock resistance, non-volatility and pollution-free, is widely used in refractory materials, ceramic materials, abrasive materials, infrared light sources, circuit capacitor materials, solar photovoltaic materials and other fields.
[0003] The preparation methods of ZrO2 include co-precipitation, hydrolysis-hydrothermal method, electrolysis method, etc.; such as prior art 1: Chinese patent application 201910609573.7 discloses a hydrothermal preparation method of nano zirconium oxide powder, wherein ZrOCl2·8H2O is dissolved in deionized water to obtain a zirconium oxychloride solution, hydrogen peroxide is added, the solution is fully stirred and placed in a hydrothermal reactor, and oxygen is introduced for hydrothermal reaction. After the reaction is completed, the solution is cooled to room temperature, discharged, filtered, and the filter cake is washed until the washing liquid is free of chloride ions, and then calcined to obtain nano zirconium oxide powder.
[0004] Prior art 1 effectively avoids the use of a precipitant, can directly prepare zirconium oxide powder under acidic conditions, saves materials, simplifies the preparation process, reduces production costs, and is suitable for large-scale stable production of zirconium oxide powder; however, since the hydrothermal synthesis method requires the use of high-temperature and high-pressure equipment, the operation is relatively unsafe, so prior art 2: Chinese patent 201010182584.0 provides a preparation process for synthesizing flaky nano zirconium oxide by precipitation method: under stirring conditions, 0.05-1 mol / L sodium borohydride solution is dropped into 0.05-1 mol / L zirconium oxychloride solution to first generate a gel, continue to titrate to generate a white precipitate, stir for 0.5-24 hours, then filter and wash the precipitate with distilled water or anhydrous ethanol for several times until the washing liquid is neutral, dry the obtained powder at 50-90°C, and calcine at 500-900°C for 2 hours to obtain flaky nano zirconium oxide powder.
[0005] Prior art 2 adopts a precipitation method to prepare zirconium oxide. However, since its purpose is to prepare flaky zirconium oxide powder, its solution does not need to pay much attention to the control of particle size distribution. However, in product applications in the field of circuit capacitor materials, the particle size distribution of zirconium oxide powder, which is one of the upstream products, is required to be relatively high. The more uniform the particle size distribution of zirconium oxide powder is, the better the performance of downstream products prepared using it will be. Summary of the invention
[0006] One of the purposes of the present invention is to provide a method for preparing zirconium oxide powder with uniform particle size distribution, wherein the prepared zirconium oxide powder has uniform particle size distribution, and during the preparation process, the excessive growth and agglomeration of particles can be minimized by slow-release sedimentation, and a specific sand grinding process can be used to synergistically improve the uniformity of the particles.
[0007] Another object of the present invention is to provide a zirconium oxide powder with uniform particle size distribution, which has the advantage of uniform particle size distribution, meets the needs of downstream high-end products, and has a high market application prospect.
[0008] To achieve the above object, the present invention provides a method for preparing zirconium oxide powder with uniform particle size distribution, comprising the following steps:
[0009] Step 1: dissolving zirconium oxychloride octahydrate in water, then adding urea or ammonium bicarbonate at a temperature of 50-80° C. until the pH of the system is 7-9 for hydrolysis reaction to obtain a slurry;
[0010] Step 2: washing and concentrating the slurry in sequence to obtain a slurry with a solid content of 15-25%;
[0011] Step 3: spray drying and calcining the slurry in sequence to obtain a sintered body;
[0012] Step 4: Mix the sintered body with water to form a suspension, and sand-grind the suspension until the particle size D90 in the suspension is less than 1 μm;
[0013] Step 5: spray drying to obtain zirconium oxide powder with uniform particle size distribution;
[0014] In the step 1, the weight ratio of urea or ammonium bicarbonate to zirconium oxychloride octahydrate is 1-2:20-30.
[0015] Furthermore, the specific operation of step 1 is: dissolving zirconium oxychloride octahydrate in water, then adding urea or ammonium bicarbonate at a temperature of 50-80°C and stirring for 8-12 hours until the pH value of the system is 7-9 to obtain a slurry; wherein the mass ratio of zirconium oxychloride octahydrate to water is 2-3:10-15.
[0016] Furthermore, the specific operation of step 2 is: repeatedly washing the slurry with pure water until the conductivity is less than 150 μs / cm, and then concentrating the slurry to obtain a slurry with a solid content of 15-25%.
[0017] Furthermore, the specific operation of the spray drying in step 3 and step 5 is: spray drying is performed under the conditions of an inlet temperature of 220-240° C., an outlet temperature of 100-120° C., and an atomizer speed of 20000-26000 Hz to obtain a powder.
[0018] Furthermore, the specific operation of the calcination treatment is: calcining the powder obtained by spray drying at 1000-1200° C. for 8-10 hours to obtain a sintered body.
[0019] Furthermore, the specific operation of step 4 is: the sintered body and pure water are prepared into a suspension in a weight ratio of 1:2-4, and sand milled for 10-30 times at a sand milling speed of 1500-2000RPM and a feed rate of 5-10L / min until the particle size D90 in the suspension is less than 1μm.
[0020] The present invention also provides a zirconium oxide powder with uniform particle size distribution, which is prepared by the above-mentioned method for preparing the zirconium oxide powder with uniform particle size distribution.
[0021] Beneficial Effects
[0022] Compared with the prior art, the present invention has at least the following advantages:
[0023] (1) The present invention uses urea or ammonium bicarbonate to slowly precipitate zirconium ions under a specific pH environment, so that the crystal nuclei are evenly dispersed and grow slowly during the precipitation process, reducing the agglomeration phenomenon, thereby obtaining a Zr(OH)4 precursor with uniform particle size and less agglomeration;
[0024] (2) The urea or ammonium bicarbonate of the present invention not only plays a role in slowly precipitating zirconium ions, but also plays a role in adjusting the pH environment. Through the pH adjustment of urea or ammonium bicarbonate, the dispersibility of the Zr(OH)4 precursor can be maximized, so that the particle size distribution of the final zirconium oxide powder is more uniform;
[0025] (3) The present invention improves the dispersibility of the Zr(OH)4 precursor by adding urea or ammonium bicarbonate during the hydrolysis reaction, and combines it with a frosting treatment to make the particle size distribution of the final zirconium oxide powder more uniform. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The present invention is further described below in conjunction with the accompanying drawings and embodiments;
[0027] Figure 1 is a PSD diagram of Example 1 of the present invention;
[0028] Figure 2 is the PSD diagram of Example 2 of the present invention;
[0029] Figure 3 is the PSD diagram of Example 3 of the present invention;
[0030] Figure 4 is the PSD diagram of Example 4 of the present invention;
[0031] Figure 5is the PSD diagram of Example 5 of the present invention;
[0032] Figure 6 It is the PSD diagram of Comparative Example 1 of the present invention;
[0033] Figure 7 It is the PSD diagram of Comparative Example 2 of the present invention;
[0034] Figure 8 It is the PSD diagram of Comparative Example 3 of the present invention;
[0035] Fig. 9 It is the PSD diagram of Comparative Example 4 of the present invention;
[0036] Fig.10 It is the PSD diagram of Comparative Example 5 of the present invention;
[0037] Fig.11 It is the PSD diagram of Comparative Example 6 of the present invention. DETAILED DESCRIPTION
[0038] The present invention will be further described below in conjunction with embodiments, but this does not constitute any limitation to the present invention. Any limited number of modifications made within the scope of the claims of the present invention are still within the scope of the claims of the present invention.
[0039] In order to explain the technical content of the present invention in detail, further description is given below in conjunction with the implementation modes.
[0040] In the following examples and comparative examples, unless otherwise specified, the parts and % refer to parts by weight and percentage by weight, respectively.
[0041] In the following examples and comparative examples, the specific operation of the spray drying is: spray drying is performed under the conditions of an inlet temperature of 220° C., an outlet temperature of 100° C., and an atomizer rotation speed of 22000 Hz to obtain a powder.
[0042] It should be noted that in the following examples and comparative examples, if the sintered body obtained in step 3 is less than 100 parts, steps 1 to 4 may be performed again to make the sintered body available in step 4 ≥ 100 parts.
[0043] Example 1
[0044] A zirconium oxide powder with uniform particle size distribution is prepared by the following steps:
[0045] Step 1: dissolving 80 parts of zirconium oxychloride octahydrate in 400 parts of water, then adding 4 parts of urea at a temperature of 50° C. and stirring for 8 hours until the pH of the system reaches 7.8 to obtain a slurry;
[0046] Step 2: repeatedly washing the slurry with pure water until the conductivity is less than 150 μs / cm, and then concentrating the slurry to obtain a slurry with a solid content of 15%;
[0047] Step 3: spray drying the slurry to obtain a powder, and then calcining the powder at 1000° C. for 10 h to obtain a sintered body;
[0048] Step 4: 100 parts of the sintered body and 400 parts of pure water were prepared into a suspension, and a 0.5 mm zirconium ball was used to perform sand milling 25 times at a sand milling speed of 1500 RPM and a feed rate of 6 L / min until the particle size D90 in the suspension was less than 1 μm;
[0049] Step 5: spray-dry the suspension obtained in step 4 to obtain zirconium oxide powder with uniform particle size distribution.
[0050] Example 2
[0051] A zirconium oxide powder with uniform particle size distribution is prepared by the following steps:
[0052] Step 1: dissolving 100 parts of zirconium oxychloride octahydrate in 500 parts of water, then adding 6 parts of urea at a temperature of 65° C. and stirring for 10 hours until the pH of the system reaches 8 to obtain a slurry;
[0053] Step 2: repeatedly washing the slurry with pure water until the conductivity is less than 150 μs / cm, and then concentrating the slurry to obtain a slurry with a solid content of 20%;
[0054] Step 3: spray drying the slurry to obtain a powder, and then calcining the powder at 1000° C. for 10 h to obtain a sintered body;
[0055] Step 4: 100 parts of the sintered body and 400 parts of pure water were prepared into a suspension, and a 0.5 mm zirconium ball was used to perform sand milling 20 times at a sand milling speed of 1700 RPM and a feed rate of 8 L / min until the particle size D90 in the suspension was less than 1 μm;
[0056] Step 5: spray-dry the suspension obtained in step 4 to obtain zirconium oxide powder with uniform particle size distribution.
[0057] Example 3
[0058] A zirconium oxide powder with uniform particle size distribution is prepared by the following steps:
[0059] Step 1: dissolving 120 parts of zirconium oxychloride octahydrate in 600 parts of water, then adding 8 parts of urea at a temperature of 80° C. and stirring for 12 hours until the pH value of the system is 9 to obtain a slurry;
[0060] Step 2: repeatedly washing the slurry with pure water until the conductivity is less than 150 μs / cm, and then concentrating the slurry to obtain a slurry with a solid content of 20%;
[0061] Step 3: spray drying the slurry to obtain a powder, and then calcining the powder at 1000° C. for 10 h to obtain a sintered body;
[0062] Step 4: 100 parts of the sintered body and 400 parts of pure water were prepared into a suspension, and a 0.5 mm zirconium ball was used to perform sand milling for 18 times at a sand milling speed of 2000 RPM and a feed rate of 10 L / min until the particle size D90 in the suspension was less than 1 μm;
[0063] Step 5: spray-dry the suspension obtained in step 4 to obtain zirconium oxide powder with uniform particle size distribution.
[0064] Example 4
[0065] A zirconium oxide powder with uniform particle size distribution is prepared by the following steps:
[0066] Step 1: dissolving 85 parts of zirconium oxychloride octahydrate in 400 parts of water, then adding 5 parts of urea at a temperature of 55° C. and stirring for 9 hours until the pH of the system reaches 8.5 to obtain a slurry;
[0067] Step 2: repeatedly washing the slurry with pure water until the conductivity is less than 150 μs / cm, and then concentrating the slurry to obtain a slurry with a solid content of 18%;
[0068] Step 3: spray drying the slurry to obtain a powder, and then calcining the powder at 1000° C. for 10 h to obtain a sintered body;
[0069] Step 4: 100 parts of the sintered body and 400 parts of pure water were prepared into a suspension, and a 0.5 mm zirconium ball was used to perform sand milling 20 times at a sand milling speed of 1600 RPM and a feed rate of 7 L / min until the particle size D90 in the suspension was less than 1 μm;
[0070] Step 5: spray-dry the suspension obtained in step 4 to obtain zirconium oxide powder with uniform particle size distribution.
[0071] Example 5
[0072] The method is generally the same as Example 1, except that the urea is replaced by ammonium bicarbonate.
[0073] Comparative Example 1
[0074] The method is generally the same as Example 1, except that the urea is replaced by sodium hydroxide.
[0075] Comparative Example 2
[0076] The method is substantially the same as Example 1, except that step 1 is changed to: dissolving 80 parts of zirconium oxychloride octahydrate in 400 parts of water, then adding 4 parts of urea at a temperature of 50° C. and stirring for 8 hours until the pH value of the system is 6 to obtain a slurry.
[0077] Comparative Example 3
[0078] The method is substantially the same as Example 1, except that step 1 is changed to: dissolving 80 parts of zirconium oxychloride octahydrate in 400 parts of water, then adding 6 parts of urea at a temperature of 50° C. and stirring for 12 hours until the pH of the system reaches 9.5 to obtain a slurry.
[0079] Comparative Example 4
[0080] The method is generally the same as Example 1, except that step 1 is changed to: dissolving 80 parts of zirconium oxychloride octahydrate in 400 parts of water, then adding 4 parts of urea at a temperature of 40° C. and stirring for 8 hours until the pH value of the system is 7.8 to obtain a slurry.
[0081] Comparative Example 5
[0082] The method is substantially the same as Example 1, except that step 1 is changed to: dissolving 80 parts of zirconium oxychloride octahydrate in 400 parts of water, then adding 4 parts of urea at a temperature of 85° C. and stirring for 8 hours until the pH of the system reaches 7.8 to obtain a slurry.
[0083] Comparative Example 6
[0084] It is generally the same as Example 1, except that step 1 is changed to: 80 parts of zirconium oxychloride octahydrate are dissolved in 400 parts of water, and at a temperature of 50° C., ammonia water is first added to adjust the pH of the system to 4, and then 4 parts of urea are added and stirred for 8 hours until the pH of the system is 7.8 to obtain a slurry.
[0085] Results
[0086] 1. Powder uniformity detection
[0087] Detection method: The bulk ratio of the product was analyzed and detected by the funnel method, the BET of the product was analyzed and detected by the static volumetric method, and the particle size of the product was analyzed and detected by Malvern Mastersizer 3000 laser particle size analyzer to obtain particle size data and PSD distribution diagram.
[0088] Examples 1-5 and Comparative Examples 1-6 were tested according to the above test method. The results are shown in Tables 1 and Figure 1-11 As shown;
[0089] Table 1 Data of zirconium oxide powders prepared in Examples 1-5 and Comparative Examples 1-6
[0090]
[0091]
[0092] According to Table 1 and Figure 1-11 The results show that:
[0093] According to the data in Table 1 of Examples 1-5, combined with Figure 1-5 It can be seen from the PSD graph that the present invention achieves a specific pH range by adding urea or ammonium bicarbonate, and slowly precipitates zirconium ions under this pH environment, so that the grains will not locally agglomerate significantly during the precipitation of zirconium hydroxide, thereby improving the uniformity of the zirconium hydroxide particles.
[0094] According to the data comparison between Example 1 and Comparative Example 1, if sodium hydroxide is used as a precipitant and a pH regulator, the bulk ratio of the zirconium oxide powder obtained is significantly increased, the BET is significantly reduced, and the particle size of the zirconium oxide powder is also significantly increased. Figure 1 and Figure 6 From the comparison of the PSD graphs, it can be seen that the uniformity of the zirconium oxide particle size distribution obtained in Comparative Example 1 is lower than that in Example 1 of the present invention. The possible reason is that sodium hydroxide is a strong alkaline substance, which directly ionizes hydroxide ions in the solution and quickly combines with zirconium ions to form Zr(OH)4 precipitation. This rapid precipitation process causes excessive precipitation of zirconium ions in local areas, uneven distribution of zirconium ion concentration in the solution, inconsistent particle growth rates, and different sizes of particles, resulting in the following situations:
[0095] 1) When larger particles are mixed with smaller particles, the gaps between the particles are relatively large, thereby increasing the bulk ratio; at the same time, the precipitation process of sodium hydroxide is rapid, which may cause the particles to partially agglomerate at the beginning of precipitation. These agglomerates are difficult to completely disperse in the subsequent treatment process, which reduces the overall packing density and increases the bulk ratio;
[0096] 2) Due to rapid precipitation and possible agglomeration, the particle surface may be rough and the particle size distribution is uneven, and the proportion of larger particles increases, which reduces the total surface area per unit mass of particles and thus reduces the BET;
[0097] 3) The particle size distribution of the formed precursor is uneven, the proportion of larger particles increases, so the particle size increases and the distribution is uneven;
[0098] The comparison between Example 1 and Comparative Example 1 proves that the particle size and uniformity of the particle size of the zirconium oxide finally obtained can be effectively controlled by using urea or bicarbonate as a slow-release precipitant and a pH regulator during the hydrolysis process of zirconium hydroxide.
[0099] In order to further study whether urea or bicarbonate only needs to play the role of a slow-release precipitant in the hydrolysis reaction, whether the pH environment is not adjusted or adjusted by other means, the present invention verifies the importance of urea in the pH adjustment process by comparing Example 1 with Comparative Example 2, Comparative Example 3, and Comparative Example 6.
[0100] According to the data comparison between Example 1 and Comparative Example 2, when the pH environment of the hydrolysis reaction is lower than 7, the bulk ratio of the obtained zirconium oxide powder increases significantly, the BET decreases significantly, and the particle size of the zirconium oxide powder increases significantly. Although it is improved compared with Comparative Example 1, it is not obvious compared with Example 1 of the present invention. Figure 1-5 and Figure 7 From the comparison of the PSD graphs, it can be seen that the technical solution of the present invention needs to be adjusted to a specific pH environment by urea or bicarbonate to carry out the hydrolysis reaction in order to significantly improve the particle size uniformity of the zirconium oxide powder. However, the pH of Comparative Example 2 is too low, which may lead to incomplete precipitation of zirconium ions during the hydrolysis process, resulting in the following situation:
[0101] 1) Some zirconium ions remain in the solution, resulting in a decrease in the number of particles formed. When these particles are piled up, the gaps between the particles are relatively large due to the insufficient number, thereby increasing the loose ratio;
[0102] 2) Incomplete precipitation reduces the number of particles, the total surface area of particles per unit mass, and thus the BET decreases;
[0103] 3) The sedimentation rate may change, resulting in uneven particle growth. Some particles may grow rapidly in a short period of time, while the growth of other particles is inhibited, resulting in uneven particle size distribution and an increase in the overall particle size.
[0104] At the same time, according to the data comparison of Example 1 and Comparative Example 3, when the pH environment of the hydrolysis reaction is too high, it will also lead to negative effects on the bulk ratio, BET and particle size of the zirconium oxide powder. Figure 1 and Figure 8 Compared with the PSD graph, a too high pH environment will cause the particle size distribution of zirconium oxide to be no longer uniform. The reasons may be:
[0105] (1) Excessive addition of urea accelerates the sedimentation rate, resulting in large-scale agglomeration of local particles and a significant decrease in the uniformity of particle distribution;
[0106] (2) OH - The concentration increases significantly, resulting in an accelerated nucleation rate, producing a large number of zirconium hydroxide nuclei in a short period of time. Since these nuclei are formed at a similar time, they will compete for limited solutes during the subsequent growth process, resulting in inconsistent growth rates, and thus uneven particle size distribution of the final zirconium oxide particles.
[0107] (3) Too high a pH value may disrupt the balance between the electrostatic repulsion and van der Waals attraction between particles, causing particles to easily agglomerate or collide, affecting the normal growth of the particles and causing uneven particle size distribution.
[0108] Furthermore, in Comparative Example 6, ammonia water was used to adjust the pH environment, and urea was used for slow release precipitation. However, according to the data in Table 1 and Fig.11 It was found that the technical solution of Comparative Example 6 led to a significant deterioration in various data and particle size distribution uniformity of the zirconium oxide powder. The reason may be that: the initial ammonia water ionizes hydroxide, accelerates the precipitation rate, and crystal nuclei are quickly generated in a short period of time. These crystal nuclei will collide with each other before they can be evenly dispersed in the solution, increasing the possibility of agglomeration. Adding urea will cause the newly generated zirconium hydroxide precipitate to grow on the existing crystal nuclei or agglomerates, further aggravating the agglomeration phenomenon.
[0109] Combining the situations of Example 1 and Comparative Examples 2, 3 and 6, it can be seen that the urea or bicarbonate of the present invention needs to play the role of a slow-release precipitant and a pH regulator at the same time in order to control the uniformity, particle size and other properties of the final zirconium oxide powder.
[0110] According to the data comparison between Example 1 and Comparative Examples 4 and 5, Figure 1 and Fig. 9 , Fig.10 From the comparison of the PSD graphs, it can be seen that the temperature of the hydrolysis reaction also has a certain influence on the quality of the final product. Although it has been improved compared with other comparative examples, the uniformity, bulk ratio, BET, particle size and other properties of the final zirconia powder are still significantly deteriorated.
[0111] When the hydrolysis temperature of Comparative Example 4 is too low, the following situations may occur:
[0112] 1) The reaction between zirconium ions and urea cannot be fully carried out, which may lead to a prolonged particle growth time and the formation of irregularly shaped particles. When these irregularly shaped particles are piled up, the gaps between the particles are large, which increases the bulk ratio;
[0113] 2) The particle surface may not be smooth enough and the roughness may increase, which will reduce the total surface area of the particles per unit mass and thus reduce the BET;
[0114] 3) It may lead to an imbalance in the nucleation and growth stages during the particle growth process. Some particles may nucleate at an early stage and grow rapidly, while other particles nucleate later and grow slowly, resulting in an uneven particle size distribution and an increase in the overall particle size.
[0115] However, the hydrolysis temperature of Comparative Example 5 is too high, which may result in the following situations:
[0116] 1) Too high temperature causes the ionization rate of ammonia in urea to accelerate, thereby increasing the precipitation rate and rapidly generating crystal nuclei in a short period of time. In the subsequent growth process, these crystal nuclei have inconsistent growth rates under limited raw material supply, resulting in uneven particle size distribution. In addition, too high temperature increases the surface energy of the particles, which makes it easier for the particles to agglomerate. The agglomerated particles are of different sizes, which leads to uneven particle size distribution.
[0117] 2) Too high a temperature is conducive to the growth and perfection of crystals, which may make the internal structure of the particles more compact, increase the mass per unit volume, and increase the bulk ratio;
[0118] 3) Too high temperature leads to faster particle growth and more agglomeration, which increases the particle size and reduces BET.
[0119] 2. Powder purity detection
[0120] Detection method: The GDMS method is used to analyze and detect the content of impurity elements in the product.
[0121] Examples 1-5 and Comparative Examples 1-6 were tested according to the above test method, and the results are shown in Table 2;
[0122] Table 2 Purity test results of zirconium oxide powder prepared in Examples 1-5 and Comparative Examples 1-6
[0123] Test samples Total impurity content detected (ppm) Example 1 <192.49 Example 2 <234.38 Example 3 <235.15 Example 4 <220.89 Example 5 <231.39 Comparative Example 1 <305.12 Comparative Example 2 <299.53 Comparative Example 3 <275.74 Comparative Example 4 <287.05 Comparative Example 5 <289.63 Comparative Example 6 <268.28
[0124] According to the results in Table 2, we can see that:
[0125] According to Examples 1-5, it is shown that the technical solution of the present invention can not only effectively improve the particle size uniformity of zirconium oxide powder, control the particle size distribution of zirconium oxide powder, but also effectively improve the purity of zirconium oxide powder. The impurity content of Comparative Examples 1, 3, 5, and 6 is significantly improved compared with that of Example 1. The possible reason is that the rapid precipitation process of Comparative Examples 1, 3, 5, and 6 will cause excessive precipitation of zirconium ions in local areas, and the concentration distribution of zirconium ions in the solution is uneven. The uneven precipitation may be mixed with unreacted substances, affecting the purity of the powder;
[0126] The impurity content of Comparative Examples 2 and 4 is also significantly increased compared to Example 1. The possible reason is that too low pH or too low hydrolysis reaction temperature causes incomplete precipitation of zirconium ions during the hydrolysis process, making the unprecipitated zirconium salt wrapped in the particles difficult to completely remove.
[0127] The embodiments presented herein are only embodiments selected according to the combination of all possible embodiments. The appended claims should not be limited by the embodiments describing the present invention. Some numerical ranges used in the claims include sub-ranges therein, and the changes in these ranges should also be covered by the appended claims.
Claims
1. A method for preparing zirconium oxide powder with uniform particle size distribution, characterized in that: The steps include: Step 1: dissolving zirconium oxychloride octahydrate in water, then adding urea or ammonium bicarbonate at a temperature of 50-80° C. until the pH of the system is 7-9 for hydrolysis reaction to obtain a slurry; Step 2: washing and concentrating the slurry in sequence to obtain a slurry with a solid content of 15-25%; Step 3: spray drying and calcining the slurry in sequence to obtain a sintered body; Step 4: Mix the sintered body with water to form a suspension, and sand-grind the suspension until the particle size D90 in the suspension is less than 1 μm; Step 5: spray drying to obtain zirconium oxide powder with uniform particle size distribution; In the step 1, the weight ratio of urea or ammonium bicarbonate to zirconium oxychloride octahydrate is 1-2:20-30.
2. The method for preparing zirconium oxide powder with uniform particle size distribution according to claim 1, characterized in that: The specific operation of step 1 is: dissolving zirconium oxychloride octahydrate in water, then adding urea or ammonium bicarbonate at a temperature of 50-80° C. and stirring for 8-12 hours until the pH value of the system is 7-9 to obtain a slurry; wherein the mass ratio of zirconium oxychloride octahydrate to water is 2-3:10-15.
3. The method for preparing zirconium oxide powder with uniform particle size distribution according to claim 1, characterized in that: The specific operation of step 2 is: repeatedly washing the slurry with pure water until the conductivity is less than 150 μs / cm, and then concentrating the slurry to obtain a slurry with a solid content of 15-25%.
4. The method for preparing zirconium oxide powder with uniform particle size distribution according to claim 1, characterized in that: The specific operation of the spray drying in step 3 and step 5 is: spray drying is performed under the conditions of an inlet temperature of 220-240° C., an outlet temperature of 100-120° C., and an atomizer speed of 20000-26000 Hz to obtain a powder.
5. The method for preparing zirconium oxide powder with uniform particle size distribution according to claim 1, characterized in that: The specific operation of the calcination treatment is: calcining the powder obtained by spray drying at 1000-1200° C. for 8-10 hours to obtain a sintered body.
6. The method for preparing zirconium oxide powder with uniform particle size distribution according to claim 1, characterized in that: The specific operation of step 4 is: prepare the sintered body and pure water into a suspension according to a weight ratio of 1:2-4, and perform sand milling for 10-30 times at a sand milling speed of 1500-2000RPM and a feed rate of 5-10L / min until the particle size D90 in the suspension is less than 1μm.
7. A zirconium oxide powder with uniform particle size distribution, characterized in that: The powder is prepared by the method for preparing zirconium oxide powder with uniform particle size distribution as described in any one of claims 1 to 6.
Citation Information
Patent Citations
Preparation process for synthesizing flaky nano zirconia by precipitation
CN101830507A
Hydrothermal preparation method of nano-zirconia powder
CN110228819A